The relationship of a family history of heart disease to awareness of risk factors among high school students - Stevens, Millicent (My University, 1986)
This study examined knowledge of heart disease, risk factors, and behaviors and physical conditions impacting heart disease among four high school students with a family history of heart disease compares with four high school students serving as controls drawn from a sample size of 156 high school students. The students were compared on their Health Assessment Questionnaire (HAQ) scores, systolic blood pressures, diastolic blood pressures, dietary cholesterol intake, height/weight, cigarette smoking, sports participation, and exercise in thier leisure time. The point-biserial and phi correlation coefficients were used to assess the relationships among the case and control groups on the variables measured. It was concluded that there were no significant relationships measures when comparing the two groups on their knowledge of heart disease, risk factors, and behaviors and physical conditions impacting on heart disease. Further, risk factors known to increase the chance of heart disease were present among the case and control high school students. Finally, the case students' HAQ scores indicated a need for more practical application of their knowledge to possibly decrease their risk of heart disease.
Keywords: Heart -- Diseases -- Prevention